Developing Monitoring System on Street Light Using GPRS Communication and Web Interface - Handayani, Rini; Ike Sari, Marlindia; Setiawan, Heri; Baskoro, Agung (International Journal of Engineering and Technology, 2019)
Public street lighting is one of infrastructure to support people activities in the evenings and also increase the safety factor in the region. However, street lighting is still inappropriate in some remote villages. It has not received adequate electricity supply and has not good internet connection which mean only has GPRS internet connection. So that, developing street light by utilizing the sufficient energy system is needed to build. Internet of Things also take a role in this system by developing monitoring system via GPRS. Monitoring system is also needed to collect the electrical and location information from devices so that central office could keep in check. It also ease the user to do troubleshoot and maintenance those devices. In this research the result was to deploy a self-sufficient public street lamp and its monitoring system using GPRS communication and web interface.Â Â